Country Difference in Preschooler’s Social Skills between Indonesia and Japan - Meriyandah, Hilda; Nurdiantami, Yuri; Zhu, Zhu; Xiang, Li; Yanlin, Wang; Tokie, Anme; Suryani, Rotua; Bunga, Dinda Nur Fajri Hidayati; Agustina, Lisna (Program Studi Pendidikan Islam Anak Usia Dini, Institut Agama Islam Ma'arif (IAIMNU) Metro Lampung, 2025)
The comparative analysis of children's social skills between Indonesia and other countries remains limited due to the scarcity of standardized tools in different countries. This study evaluates the association of cross-country differences, age, and gender with children's social skills in Indonesian and Japanese by using the exact measurement: Social Skill Scale-24, which consists of 3 sub-scales (assertion, self-control, cooperation) and 24 items. The data was collected in Indonesia from nine kindergartens in B City, West Java. The Japanese data was obtained from the Child Cohort Study (CCC), collected in 2022. Finally, there were 1436 participants, with 1157 participants from Japan and 279 from Indonesia. Our findings indicate that country difference is significantly associated with children's social skills (p<0.05). Indonesian children demonstrated stronger cooperation skills, whereas Japanese children excelled in assertion, self-control, and the overall SSS score. In addition, children's age and gender were significantly associated with preschoolers' social skills in both samples. Furthermore, all items in SSS-24 achieved satisfactory CFA scores (>0.5), and the omega coefficients for the total scores above 0.9 in Indonesia and Japan imply this questionnaire is valid and reliable. These findings suggest that best practices from each country can be adapted to local cultural contexts to improve children's social skills.